Evaluation of the quality of the soils In sugarcane cultivars (saccharum officinarum L.) in the parish fatima province of Pastaza - González, Víctor (2019)
Being the ground resource one of the fundamental components that provides goods and services for the development of life, to meet the food need in the present times, demand for larger areas with monoculture, this is the reason for the degradation of ecosystems natural; The object of the study was to evaluate the quality of soils in sugarcane cultivars (Saccharum officinarum L.) in the Fatima province parish, Pastaza province. Samples of six randomly selected agricultural production units were collected, at 25-30 cm depth. The parameters evaluated were% W, Ca2+, Mg2+, Na+, pH, MO and CE. Salinity analysis was developed by atomic absorption spectrophotometry. The pH results (3.84 to 4.72) of the soils of the area revealed to be strongly acidic; with CE (0.36 to 2.02 mS/cm) denoting low salinity Ca2+ (0.122 to 0.210 meq/100ml), Mg2+ (0.022 to 0.046 meq/100ml) and Na+ (0.031 to 0.049 meq/100ml) with sodium being responsible for increasing EC in soils, MO content (12.1 - 12.7%); Nutrients P (5.80 to 14.00 ppm), K (0.12 to 0.36 meq/100ml), Ca (1.90 to 5.00 meq/100ml), Mg (0.60 to 1.30 meq/100ml) and moisture content (% W) (128.04 a 238.22%) which are environmental characteristics of the Ecuadorian Amazon. The progressive deterioration of soils in the parish of Fatima is due to poor agricultural practice and poor agricultural technologies